IMPLEMENTING VAKT METHOD FOR TEACHING ENGLISH READING TO DYSLEXIA STUDENTS - Ni Luh Putu Novi Wulandari (English Department, STKIP PGRI Bandar Lampung, 2020)
There are four skills that should be mastered in English, namely listening, speaking, writing, and reading. People should do a lot of practice for mastering those skills, including the students with special needs. Dyslexia students usually have problems in reading, knowing, and pronouncing the words. This study aims to review the use of Visual, Auditory, Kinesthetic, and Tactile (VAKT) in teaching reading skill for students with dyslexia. The study is a library study that focuses on collecting the theoretical and empirical studies about VAKT for teaching reading skill to dyslexia students. Visual, Auditory, Kinesthetic, and Tactile (VAKT) is a method that is used to help dyslexia students in improving their reading skill. This study finds that the use of VAKT is effective teaching method to Dyslexia students because this method helps Dyslexia students to improve their reading skill.